EVALUATION OF ANTIMICROBIAL AND BIOACTIVE POTENTIALS OF TELFAIRIA OCCIDENTALIS ON MICROORGANISMS - Nnamonu, Emmanuel Ikechukwu (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
The intensification of numerous deadly diseases like infections by multidrug-resistant bacteria suggests re-inventing the wheel on drug discovery. Indeed, countless disparate studies have underscored substitutes for combating the effects of antibiotic resistance. For many decades, plants have assumed an essential alternative medicine, demonstrated to be effective in human healthcare. The use of plants as alternative antibiotics in controlling some illnesses has attracted considerable research attention. The present paper investigates the phytochemical contents and the antimicrobial action of T. occidentalis on microorganisms. In particular, the study examined its effect on Candida albicans, Staphylococcus aureus, and Pseudomonas aeruginosa. The outcome of the phytochemical analysis performed on the seed and leaf of T. occidentalis indicated the presence of tannin, alkaloids, steroids, flavonoids, saponins, and phenol. However, it was found that phenol and tannins were primarily deposited in the plant's seed. Similarly, the antimicrobial analysis showed that S. aureus was more susceptible to the acetone, ethanol, and hot aqueous extracts of T. occidentalis. Furthermore, Candida albicans and Pseudomonas aeruginosa showed sensitivity to acetone and ethanol but did not react to the hot aqueous extracts. The study's findings reveal that the biological responses elicited by T. occidentalis aqueous extracts support the plant's historical use as an alternative antibiotic.